Deities depicted on the Shikhara of the Rangamandapa - Temples of India Project Team (Jio Institute, 2024)
The pediment of the rangamandapa’s (open type of pillared hall) shikhara (superstructure) depicts other gods, including Surya and Vishnu. A standing figure of Surya and Vishnu can be seen on the pediment. A bejewelled Surya holds fully bloomed flowers in his two arms. The four-armed Vishnu is holding his respective weapons with one of his hands in varadahasta (boon-giving gesture) in which he holds an akshamala (rosary). Both deities are flanked by female figures.